2020
DOI: 10.1186/s12879-020-4950-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial otitis media in sub-Saharan Africa: a systematic review and meta-analysis

Abstract: Background: Otitis media is inflammation of the middle ear, comprising a spectrum of diseases. It is the commonest episode of infection in children, which often occurs after an acute upper respiratory tract infection. Otitis media is ranked as the second most important cause of hearing loss and the fifth global burden of disease with a higher incidence in developing worlds like Sub-Saharan Africa and South Asia. Therefore, this systematic review is aimed to quantitatively estimate the current status of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 54 publications
(49 reference statements)
6
29
1
1
Order By: Relevance
“…are the most cited causative agents for otitis in sub-Sharan Africa and are reported to exhibit a high level of resistance to multiple antibiotics. 20 On the other hand, the majority of the participants were women of reproductive age, which explains the high number of urine specimens and E. coli processed in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…are the most cited causative agents for otitis in sub-Sharan Africa and are reported to exhibit a high level of resistance to multiple antibiotics. 20 On the other hand, the majority of the participants were women of reproductive age, which explains the high number of urine specimens and E. coli processed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…19 Ear pus, urine, wound pus, stool, and blood specimens were the most frequent clinical specimens analyzed. The presence of a large number of ear pus specimen points toward suppurative otitis diseases which are common in children and adolescents below 15 years especially in sub-Saharan Africa, 20 and their transmission is linked to poor hygienic conditions. P. aeruginosa, S. aureus, Proteus spp., and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 7 Although P. aeruginosa has been reported to be the leading cause of CSOM followed by S. aureus by many investigators but variation in bacterial profile and frequency is well documented. 10 , 11 , 20 The conducive environment of middle ear cavity may favour the growth of P. aeruginosa but etiological agents of CSOM differs substantially with regards to time and place and also factors like variation in climate, socioeconomic status and patient’s self-hygiene play important role. 11 We observed polymicrobial infections in 7.3% cases, which is a very common occurrence in CSOM and many studies have reported mixed pathogens including bacteria and fungus.…”
Section: Discussionmentioning
confidence: 99%
“…reported high level of resistance against Ampicillin, Amoxicillin/Clavulanate, Cotrimoxazole, Amoxicillin, and Cefuroxime and our finding is in concordance with this report and also in agreement with another recent study. 10 , 20 Moderate to high resistance observed against different classes of antibiotics indicates prevalence of MDR bacteria and is a matter of great concern because antibiotics from these classes are being prescribed frequently for empirical treatment of CSOM. Unethical prescription of antibiotic for trivial causes, easy availability over the counter, lack of culture facilities and absence of good governess are all contributing factors in the development of high antimicrobial resistance (AMR) in the developing countries including Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation